Total Sialic Acid (TSA) Level as a Tumor Marker in the Diagnosis of Oral Cancer - Hafiz Muhammad Rafique Tagar; Muhammad Iltaf; Hoor Fatima; Nudrat Anwar Zuberi; Shahnaz Imdad Kehar (Journal of Bahria University Medical and Dental College)
Objective: To estimate serum Total Sialic Acid (TSA) levels in different grades of oral squamous cell carcinoma and to access it`s utility as a tumor marker in this cancer. Materials and Methods: This study was conducted in 68 adult subjects equally divided into two groups, healthy individuals and patients with oral squamous cell cancer. Under aseptic precautions venous blood was drawn and serum was separated.Estimation of serum total sialic acid level was done according to Spectrophotometeric method of Plucinsky. Statistical analysis was carried out by using SPSS 19. Results: Total subjects in the study included were 58.82% males and 41.17% females. Mean age of oral cancer patients was 48.05 ± 8.82 years. There was significant male predominance with P<0.05. Oral cancer was most common in Tobacco+ Chaliya + Areca nut and Gutka+pan groups. Mean serum total sialic acid (TSA) level in control group was 60.2 ± 4.27 mg/dl, whereas it was 99.1 ± 18.30 mg/dl in oral cancer group. It was significantly increased in oral cancer group when compared to control group with P value < 0.01. There was progressive elevation in mean serum TSA level in oral squamous cell carcinoma, Conclusion:Estimation of serum total sialic acid level (TSA) in different grades of oral squamous cell carcinoma showed positive relation with stage of malignancy, specifically with the tumor burden. It can be used as a diagnostic biomarker in oral squamous cell cancers.